Ligand Recognition Specificity of Leukocyte Integrin α(M)β(2) (Mac-1, CD11b/CD18) and Its Functional Consequences - Podolnikova, Nataly P. (Biochemistry, 2015)
The broad recognition specificity exhibited by integrin α(M)β(2) (Mac-1, CD11b/CD18) has allowed this adhesion receptor to play innumerable roles in leukocyte biology, yet we know little about how and why α(M)β(2) binds its multiple ligands. Within α(M)β(2), the α(M)I-domain is responsible for integrin’s multiligand binding properties. To identify its recognition motif, we screened peptide libraries spanning sequences of many known protein ligands for α(M)I-domain binding and also selected the α(M)I-domain recognition sequences by phage display. Analyses of >1400 binding and nonbinding peptides derived from peptide libraries showed that a key feature of the α(M)I-domain recognition motif is a small core consisting of basic amino acids flanked by hydrophobic residues. Furthermore, the peptides selected by phage display conformed to a similar pattern. Identification of the recognition motif allowed the construction of an algorithm that reliably predicts the α(M)I-domain binding sites in the α(M)β(2) ligands. The recognition specificity of the α(M)I-domain resembles that of some chaperones, which allows it to bind segments exposed in unfolded proteins. The disclosure of the α(M)β(2) binding preferences allowed the prediction that cationic host defense peptides, which are strikingly enriched in the α(M)I-domain recognition motifs, represent a new class of α(M)β(2) ligands. This prediction has been tested by examining the interaction of α(M)β(2) with the human cathelicidin peptide LL-37. LL-37 induced a potent α(M)β(2)-dependent cell migratory response and caused activation of α(M)β(2) on neutrophils. The newly revealed recognition specificity of α(M)β(2) toward unfolded protein segments and cationic proteins and peptides suggests that α(M)β(2) may serve as a previously proposed “alarmin” receptor with important roles in innate host defense. [Image: see text]